2002
DOI: 10.1097/00006199-200207000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Behavioral Interventions on Disruptive Behavior and Affect in Demented Nursing Home Residents

Abstract: The treatments did not specifically address the factors that may have been triggering disruptive behaviors. Interventions much more precisely designed than those employed in this study require development to quell disruptive behaviors. Nontargeted interventions might increase positive affect. Treatments that produce even a brief improvement in affect indicate improved quality of mental health as mandated by federal law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
114
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 34 publications
2
114
0
2
Order By: Relevance
“…These issues most likely contributed to the lack of significant findings for negative affect. These findings are similar to Beck et al (2002) who found significantly more positive affect, but no reduction in negative affect or agitation, following implementation of tailored behavioral interventions for NH residents with dementia. They too found little negative affect, and concluded that their nontargeted interventions need to be more precisely designed to improve a broader range of behavioral outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…These issues most likely contributed to the lack of significant findings for negative affect. These findings are similar to Beck et al (2002) who found significantly more positive affect, but no reduction in negative affect or agitation, following implementation of tailored behavioral interventions for NH residents with dementia. They too found little negative affect, and concluded that their nontargeted interventions need to be more precisely designed to improve a broader range of behavioral outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…However, we are unable to discriminate between the treatment and placebo effect given this sample size. All individuals providing the placebo TT used a calm approach, and were using touch in a non-custodial context, which may have been interpreted by the participant as compassionate touch, or one-to-one social interaction known to have positive effects [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one RCTs met the inclusion criteria [40][41][42][43][44] and five main intervention categories emerged (Table 1): psychoeducational [13][14][15][16][17][18][19][20][21], physical activity [22][23][24][25], sensorial [26][27][28][29][30][31][32][33][34], staff-focused [35,36,37,38,40] and complex [41][42][43][44] (Table 2). Nineteen studies were two-arm RCTs [14,15,[17][18][19][21][22][23]25,26,[29][30][...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nineteen studies were two-arm RCTs [14,15,[17][18][19][21][22][23]25,26,[29][30][31][32]35,38,40,41,43] and 12 were three-arm or more [13,16,20,24,27,28,33,34,36,37,42,44].…”
Section: Study Characteristicsmentioning
confidence: 99%